IDENTIFICATION AND CONTROL OF PESTS AND DISEASES IN THE NURSERY OF PT NATARANG MINING TANGGAMUS DISTRICT - Yustika, Vidia; Indriyanto; Asmarahman, Ceng (Jurnal Rimba Lestari, 2022)
Quality seedlings are needed to increase land reclamation and rehabilitation activities. Quality seedlings are genetically, physically and physiologically superior seedlings so that they are able to adapt to critical environments. Seedlings are said to be of friendly quality, having normal growth, straight trunk, healthy and free from pests and diseases. One way to provide quality seedlings is to build a nursery like the one at PT Natarang Mining. However, the seedlings produced by this nursery are still of low quality because they are attacked by pests and diseases. In this study, an investigation of pests and diseases in the nursery of PT Natarang Mining was carried out. Data were collected by random sampling with a sampling intensity of 10% so that the sample used was 1,210 forest plant seedlings. Then carried out observations on the forest plant seedlings to see whether there are defects caused by pests and diseases. From the observations it is known that the pests and diseases that attack plant seedlings in the nursery forest of PT Natarang Mining are dominated by snail pests (26%) and leaf spot disease (16%). These pests and diseases can be overcome in several ways, including by implementing thinning activities and by using plant-based insecticides and fungicides such as garlic extract, neem leaves and others. Pest and disease control can also be done by using chemicals such as fungicides with benomyl and sulfur as an active ingredient.